Export market destination and performance: Firm-level evidence from Sub-Saharan Africa - Ousmanou Njikam (Journal of African Trade, 2017)
This paper uses a novel manufacturing firm-level survey data in 19 sub-Saharan African (SSA) countries to explore the linkages among a number of export-market destinations (e.g., China, India, other Asia, EU, US, MENA, SSA excluding South Africa, and South Africa) and performance. The paper also examines differences between exporters and non-exporters performance and assesses self-selection. We find superior characteristics of exporters relative to non-exporters. Size, foreign ownership and past export experience enhance the propensity to export while continuing exporters outperform switching ones. Export destination matters: exporting to China leads to improvements in total factor productivity (TFP); India destination enhances the wage rate, labour productivity and TFP, while the South Africa destination depresses capital intensity. Furthermore, the study finds that export intensity matters for certain destinations, with higher levels of exports to the USA improving enterprise performance, such as increases in overall output and labor productivity, while the reverse holds for exports to other SSA countries. This latter finding clearly poses a challenge to efforts to increase intra-Africa trade. These findings should provide coherent and coordinated strategies for SSA policies seeking to promote economic development through exporting and diversification of trade partners.
Keywords: F14; D21; L1; 330; Trade; Export premium; Export destination; Performance